Effectiveness of presumptive tax system in Zimbabwe: case of ZIMRA region one - Utaumire, Benjamin; Mashiri, Eukeria; Mazhindu, Kenneth (International Knowledge Sharing Platform, 2018)
The research’s main thrust was to evaluate the effectiveness of the presumptive tax system in Zimbabwe, case study –Zimra Region One. The research looked at the implementation of the tax head, setting of tax rates, collection of revenue and the views of various stakeholders. In this study 100 ZIMRA staff members, 180 informal traders and 20 local authority staff members formed the main research participants. It was established that the presumptive tax head has not been fully implemented and administered. This has seen it contributing 60% to the gross domestic product against a 3% contribution to revenue compared with other tax heads. The principal findings were that many players in the informal sector are oblivious of the existence and objective of the presumptive tax head. In addition, the absence of involvement of the concerned stakeholders in determining tax rates has resulted in spirited resistance. ZIMRA has its own shortcomings which include lack of follow ups and inadequate awareness campaigns. The study revealed that effective implementation and administration of the tax head has the potential of increasing the revenue base. This means there is room for improvement on implementation and administering of the presumptive tax.